2023
DOI: 10.1186/s12889-023-16321-3
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trend analysis of the HIV/AIDS burden before and after the implementation of antiretroviral therapy at the population level from 1990 to 2020 in Ghana

Abstract: Background Antiretroviral therapy (ART) has helped reduce the burden of human immunodeficiency virus (HIV) and acquired immune deficiency syndrome (AIDS) in the majority of countries. Its contribution to the HIV/AIDS burden in Ghana is still understudied. This study examined HIV/AIDS trends in Ghana before (1990–2004) and after (2004–2020) the implementation and expansion of ART. Methods We obtained HIV/AIDS epidemiology and treatment data for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Coupled with the introduction of ART, these measures have significantly contributed to Ghana’s reduction in new HIV infections. Notably, adult HIV incidence decreased by 5% from 2004 to 2020 [ 7 , 17 ]. Nonetheless, further improvements are needed to strengthen Ghana’s HIV prevention efforts.…”
Section: Recommendations and Strategies For Enhanced Efforts Towards ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Coupled with the introduction of ART, these measures have significantly contributed to Ghana’s reduction in new HIV infections. Notably, adult HIV incidence decreased by 5% from 2004 to 2020 [ 7 , 17 ]. Nonetheless, further improvements are needed to strengthen Ghana’s HIV prevention efforts.…”
Section: Recommendations and Strategies For Enhanced Efforts Towards ...mentioning
confidence: 99%
“…These efforts have yielded positive outcomes, including increased awareness, improved access to ART, and a reduction in new infections over the years [ 6 , 16 ]. For instance, the national HIV incidence among adults has decreased by 5% from 2004 to 2020 [ 17 ]. Moreover, a report from WHO [ 15 ] also showed that linkage to ART improved from 85% to 99% in a polyclinic in the Greater Accra region a year after the DSD SI initiative.…”
Section: Introductionmentioning
confidence: 99%